New taxa of Neotropical Geophilomorpha (Chilopoda) - Pereira, Luis Alberto (2000)
A new family (Macronicophilidae) is established for Macronicophiius Silvestri, 1 909, currently placed in Geophilidae. Seven new species of Neotropical Geophilomorpha are described: ltyphilus wucius n.sp. and I. sensibilis n.sp. (Ballophi lidae), Hyphydrophilus projectus n .sp. and Ribautia onycophaena n.sp. (Geophilidae). Macronicophilus abbreviatus n.sp. M. unguiseta n. sp. and M. venezo/anus n. sp. (Macronicophilidae). The hitherto unknown male of Schendylops marchantariae (PEREIRA. MINELLI & BARBIERI, 1995) is described and two species (Pectiniunguis geayi (BROLEMANN & RIBAUT, 1911) and ltyphilus calinus CHAMBERLIN, 1957 are redescribed from the type and new material. A key to the species of Macronico philus is provided.